HUBUNGAN ANTARA JUMLAH KELAHIRAN BALITA DENGAN JUMLAH BALITA STUNTING: CORRELATION BETWEEN TODDLER BIRTH AND THE NUMBER OF STUNTING TODDLERS - Binuko, Raafika Studiviani; Maulindar, Joni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
Disorders experienced by babies caused by stunted growth are commonly called stunting. The number of sufferers in toddlers in Indonesia is very large, so this has received the attention of the government. Several factors cause stunting in toddlers, including lack of food intake and exclusive breastfeeding in toddlers. However, the percentage and the relationship between the number of babies born and the possibility of stunting are unknown, which is the basis for this research. The purpose of this study was to determine the relationship between the number of babies born and the possibility of stunting babies. Research conducted using regression analysis is used to determine the relationship between variables. The sample data used in this study were 157 toddlers. The data collection technique used is the collection of primary data and secondary data. Based on the results of the analysis conducted by the researchers, the correlation value between the number of babies born and the number of stunted babies is 0.38 (very low category). Therefore, it can be concluded that the relationship between the number of babies born and the likelihood of stunting babies has a very low significance level.